Análise comparativa das respostas econômicas e sociais às pandemias da gripe espanhola e Covid-19 no Brasil: lições históricas e estratégias para a formulação de políticas públicas resilientes e eficazes - França Júnior, Rogerio da Silva (Universidade do Vale do Rio dos Sinos, 2024)
Throughout history, pandemics such as the Spanish Flu of 1918-1919 and COVID-19 of 2020 have brought significant impacts on global social, economic, and political structures. This study investigates and compares the economic responses adopted in Brazil during these two pandemics, aiming to identify patterns, similarities and differences in the strategies implemented. Although separated by more than a century, both pandemics required coordinated actions, revealing both the fragilities and the adaptability of governments in the face of large-scale health crises. Using a methodology of historical review and comparative analysis, the study evaluates fiscal, monetary, trade and exchange rate policies, considering their immediate and long-term effects on the Brazilian economy. The results highlight the need for an integrated and coordinated approach to mitigate the economic and social impacts of pandemics, offering recommendations based on lessons learned for the formulation of more effective and resilient public policies in the future. This study contributes to the understanding of how historical experiences can inform the development of robust universal policies, emphasizing the importane of economic flexibility and the need for continuous learning in crisis management.
Keywords: Pandemias; Gripe Espanhola; COVID-19; Políticas econômicas; Economia brasileira; Pandemics; Spanish Flu; Economic policies; Brazilian economy; ACCNPQ::Ciências Sociais Aplicadas::Economia